Fusion of General Transit Feed Specification (GTFS) and passenger count data: A case study on Cyprus Transit System - Ballis, Haris; Alogdianakis, Filippos; Nikolaou, Paraskevas; Stylianou, Katerina S.; Dimitriou, Loukas (My University, 2021)
The General Transit Feed Specification (GTFS) has become the most widely used transit data exchange format. This study fuses publicly available GTFS data for Cyprus’ transit network with corresponding travel demand data to enable a holistic evaluation of the provided services. This data fusion allows for the simultaneous evaluation of the transit system across multiple dimensions (e.g. infrastructure, network structure, strategic planning, operations, etc.) and results in significantly deeper insights and recommendations towards improving the provided transit services.
Keywords: ITS; GTFS; Transit network analysis; Data fusion